Gramática de la lengua de violencia: coming of age in R. F. Kuang’s Babel: Or the necessity of violence: An arcane history of the Oxford translators’ revolution - ElZayat, Maryam Mohamed KamalElDeen Mohamed (Kansas State University, 2024)
R.F. Kuang’s Babel: Or the Necessity of Violence: An Arcane History of the Oxford Translators’ Revolution (referred to as Babel hereafter) is a work of eclectic aesthetics that skillfully weaves together elaborate conversations in the fields of literary and linguistic studies to explore themes of colonialism, ethics of translation and language acquisition, and the complex dynamics of power. This thesis aims to unpack Babel’s commentary on colonialism, imperialism, and violence through the lens of its character development—particularly focusing on Victoire, Ramy, and Robin—and the psychological toll they endure. While Victoire, Ramy, and Robin are not the only characters navigating the moral landscape of Babel, their journeys are central to understanding the novel’s interrogation of colonialism, imperialism, violence, and resistance. In the ensuing chapters, I shall embark on an analysis of Victoire, Ramy, and Robin. Each character offers a vivid representation that encapsulates diverse aspects of the colonial experience and the path of resistance. Their transformation from states of subjugation to self-awareness and defiance provides a deep exploration of the novel’s primary themes. Furthermore, their narrative arcs do more than illustrate the characters’ experiences; they illuminate the profound and enduring existential conflicts born out of the colonial encounter. The narratives of the trio will be explored not just in isolation but also in how they intertwine to form a more holistic picture of the colonial experience and the resistance against it. In this light, Babel transcends its literary confines, evolving into a multidisciplinary record that reflects the human condition under the influence of colonialism and its enduring legacies. Chapter One, entitled “Victoire Desgraves Almost Lost in Translation: Language, Identity, and Power,” embarks on an illuminating exploration into Victoire’s diasporic account. This chapter focuses on her pursuit of self-discovery and cultural reclamation, examining her trajectory through the theoretical lens of Gayatri Chakravorty Spivak’s concept of subalternity, giving voice to her unique experiences and perspectives. The chapter also explores how Desgraves navigates the intersections of language, race, and gender, shedding light on how these factors intersect and affect her during her time in Babel and how they compelled her action toward resistance. Drawing on Spivak’s framework, the chapter highlights marginalized individuals’ challenges in asserting their agency and reclaiming their cultural heritage. Chapter Two, titled “Macaulay’s Legacy: Decoding Ramy’s Arc,” embarks upon a critical dissection of Ramy’s character and his entanglement with the colonial educational systems championed by Macaulay. This chapter navigates the intricacies of Ramy’s experiences, reflecting on how they are inextricably linked to the broader colonial discourse. It scrutinizes the challenges he faces, particularly in terms of mimicry and hybridity, engaging with the theoretical insights of Homi K. Bhabha. This examination sheds light on Ramy’s struggles and emphasizes the significance of his identity as a Muslim Indian in the narrative. Chapter Three, titled “Deciphering Robin Swift: A Fanonian Phenomenon and a Late Awakening,” delves into the life of Robin Swift. This chapter confronts the themes of violence and identity, examining Robin’s transformation from a passive figure to an active resistor of colonial violence. It explores how the violation of his mother, country, and sense of self triggers a profound change in his character. This part is analyzed through the Fanonian framework relating to violence and its impact on the colonized’s psyche, revealing how his experiences reflect broader issues of cultural commodification and exploitation under colonial rule. Why is such a work important and still relevant in the twenty-first century? To answer this question, it is crucial to understand the nature of history and literature, along with the motivations behind their intersection. History is often distorted; it is often biased, shaped by the circumstances and viewpoints of its recorders. This dynamic is further influenced by the power imbalance, where victors, regardless of their moral standing, dominate the narrative. In such contexts, akin to a black box in the flight of time, literature emerges as an alternative, veiled, and metaphorical history, especially of the oppressed. Authors skillfully weave truths about their era’s conditions and critiques of their societies into their narratives. Rhetorical language serves as a protective veil, allowing authors to subtly confront authority without fearing persecution and prosecution. The depth of Babel compels me to argue that it will serve as a commentary on the state of the twenty-first century, allowing future generations to fill in the blanks, to observe and analyze why an alternative portrayal of eighteenth-century colonial Britain remains pertinent today. However, it is essential to acknowledge that there will always be unwritten history, concealed by the complexities of human perspectives and power dynamics. Among numerous cultural instances exploring such intricate discussions, Babel, in my view, still stands out for its mastery of navigating and explaining its convoluted codes to reach the minds and hearts of academics and general readers alike. Furthermore, Kuang’s capability to create a narrative with a Victorian backdrop with all the era’s concerns and significant occurrences—including the Industrial Revolution, class disparities, child labor, Empire building, women’s rights, and the opium wars—while concurrently engaging with contemporary societal concerns is remarkable. This approach elucidates the novel’s critique of the inadequate attempts to address historical power imbalances and colonial legacies that continue to shape today’s world.
Keywords: R. F. Kuang; Babel: Or the necessity of violence: An arcane history of the Oxford translators’ revolution; Postcolonialism